The Marketing and Financial Feasibility Analysis of Agroindutry Rice Mill Business (Case Study of PP Gapsera Sejahtera Mandiri in Seputih Raman District): Marketing and Financial Feasibility Analysis of Agroindutry Rice Mill Business (Case Study of PP Gapsera Sejahtera Mandiri in Seputih Raman District) - Sutarni Sutarni; Dayang Berliana; Fitriani Fitriani; Teguh Budi Trisnanto; Varingan Prianando Tambunan; Oky Arifin (Jurnal Penelitian Pertanian Terapan, 2025)
The rice cultivation system developed in Lampung Province is still conventional, but community groups in Rejoasri Village, Seputi Raman District, Central Lampung Regency have begun to develop which have implemented sustainable agricultural practices, namely PP Gapsera Sejahtera Mandiri. One of the rice produced has the advantage of non-chemical pesticide rice. The problem faced by the value chain actors of the rice milling agroindustry business is that the business does not operate continuously due to limited stock of grain raw materials, this is due to the fact that business actors have limited warehouse capacity, limited capital, and poor marketing management. Constraints in marketing also cause the Company's cash flow to also be disrupted. For this reason, it is necessary to study whether the rice milling business of PP Gapsera Sejahtera from the market and financial aspects is feasible or not developed. The goal of this study is to analyze the marketing and financial feasibility of the PP GSM paddy rice milling business. The analysis method used is descriptive analysis of rice marketing and investment feasibility analysis using Net Present Value (NPV), Net Benefit Cost ratio (Net B/C ratio), and Internal rate of return (IRR) analysis. The results of the study show that from the marketing aspect, the rice milling business is feasible to be developed. This can be seen from the marketing pattern of Berasera rice has 3 patterns, the rice sold has the advantage of having the "Berasera" brand, namely; Rice without chemical pesticides, has a certificate from Sucofinda Rice is free of chemicals and a halal certificate. Selling prices are competitive in the market and have paid attention to the production costs incurred. The promotion strategy is carried out directly through exhibitions, social media, the Shopee marketplace, and the PP gapsera website. The distribution strategy is carried out through several patterns from producers, agents, retailers (shops/supermarkets), with the aim of expanding the rice marketing network. Judging from the financial aspect, rice milling is worth developing, because the NPV value is > 0. Net B/C ratio > 1, and IRR > The applicable bank interest rate of 7%. Keywords: Financial, feasibility, healthy rice, marketing, milling